Biochar immobilized plant growth-promoting rhizobacteria enhanced the physicochemical properties, agronomic characters and microbial communities during lettuce seedling - Guan, Ti-Kun; Wang, Qiu-Ying; Li, Jia-Shu; Yan, Hui-Wen; Chen, Qing-Jun; Sun, Jian; Liu, Chao-Jie; Han, Ying-Yan; Zou, Ya-Jie; Zhang, Guo-Qing (Frontiers in Microbiology, 2023)
Spent mushroom substrate (SMS) is the by-products of mushroom production, which is mainly composed of disintegrated lignocellulosic biomass, mushroom mycelia and some minerals. The huge output and the lack of effective utilization methods make SMS becoming a serious environmental problem. In this study, SMS derived biochar (SBC), combined plant growth-promoting rhizobacteria (PGPR, Bacillus subtilis BUABN-01 and Arthrobacter pascens BUAYN-122) and SBC immobilized PGPR (BCP) were applied in the lettuce seedling using composted SMS (CSMS) based substrate. The physicochemical properties of substrate, agronomic and physicochemical properties of lettuce and rhizospheric bacterial and fungal communities were investigated for the application of SMS and SBC. The addition of SBC and BCP significantly (P < 0.05) improved the total nitrogen and available potassium content. The 5% (v/v) BCP addition treatment (T5) represented the highest fresh weight of aboveground and underground, leave number, chlorophyll content and leaf anthocyanin content, and the lowest root malondialdehyde content. Moreover, high throughput sequencing revealed that the biochar immobilization enhanced the adaptability of PGPR. The addition of PGPR, SBC and BCP significantly enriched the unique bacterial biomarkers. The co-occurrence network analysis revealed that 5% BCP greatly increased the network complexity of rhizospheric microorganisms and improved the correlations of the two PGPR with other microorganisms. Furthermore, microbial functional prediction indicated that BCP enhanced the nutrient transport of rhizospheric microorganisms. This study showed the BCP can increase the agronomic properties of lettuce and improve the rhizospheric microbial community. It provides a new idea of SMS application.